Continuous versus interrupted abdominal wall closure after emergency midline laparotomy: CONTINT : a randomized controlled trial [NCT00544583] - Polychronidis, Georgios; Rahbari, Nuh Nabi; Bruckner, Thomas; Sander, Anja; Sommer, Florian; Usta, Selami; Hermann, Janssen; Albers, Max Benjamin; Sargut, Mine; Knebel, Phillip; Klotz, Rosa (World journal of emergency surgery, 2023)
High-level evidence regarding the technique of abdominal wall closure for patients undergoing emergency midline laparotomy is sparse. Therefore, we conducted a randomized controlled trial (RCT) to evaluate the efficacy and safety of two commonly applied abdominal wall closure strategies after primary emergency midline laparotomy.
Gesehen am 04.12.2023